Course of Diabetic Foot Infection: A Single Center Experience - Ozer Balin, Safak; Ugur, Kader (Bilimsel Tip Yayinevi, 2024)
Introduction: Both the incidence of diabetic foot lesions and the management of this patient group vary from country to country and even from region to region, depending on many factors such as socio-economic status, education level, and personal foot care. This study aimed to evaluate the clinical and laboratory findings and treatment approaches for diabetic foot infection patients and to determine the mortality and amputation rates, along with associated risk factors. We believe that presenting patient data from our region will contribute valuable insights to the existing literature. Materials and Methods: Diabetic foot infection patients were divided into subgroups as mild, moderate, and severe according to the Infectious Diseases Society of America -International Working Group on the Diabetic Foot classification. Accompanying bone infection was also noted. Patient data were collected through retrospective review. Results: Three hundred seven patients were included in the study. Sixty four point eight percent of the patients were male. While 48.2% of the patients had a moderate infection, the frequency of osteomyelitis was 37.7%. A significant difference was identified between patients with and without osteomyelitis and between the severe infection group and the mild and moderate infection groups in terms of white blood cell and C -reactive protein levels, and erythrocyte sedimentation rate. Gram-positive bacteria grew in 61.6% of deep tissue cultures. The methicillin resistance rate among all staphylococcal species was 44.1%. The in -hospital mortality rate was found to be 12.7%. While increasing neutrophil count was a predictive value for amputation, increasing age, HbA1c, and decreasing albumin levels were important predictive factors for mortality. Conclusion: Diabetic foot infection continues to be a serious health problem, especially in developing countries. Understanding the local patient data can facilitate the provision of appropriate empirical antimicrobial treatment, potentially reducing morbidity and mortality rates.
Keywords: Diabetic foot; Infection; Clinical course; Laboratory findings; Outcomes